EXPANDIRSE EN RED: CARTOGRAFÍA RIZOMÁTICA DE LOS ACTUALES MODELOS DE COLABORACIÓN, PRODUCCIÓN Y EXHIBICIÓN DEL “OTRO” CINE CONTEMPORÁNEO EN EL CONTEXTO VASCO1 - Vanesa FERNÁNDEZ-GUERRA,Estibaliz ALONSO RUIZ DE ERENTZUN (Fonseca, Journal of Communication, 2023)
This paper takes an interdisciplinary approach to the hypothesis that the nodal structure that develops between public institutions, directors and creators has enabled a network that has brought about a considerable increase in the production and exhibition of contemporary audiovisual works in the Basque Country